Users in crisis response and recovery: catharsis and social learning among social media users during and after a natural disaster. Issue 1 (2nd January 2023) - Goode, Sigi
ABSTRACT: Prior research has shown the personal catharsis benefits of social media use as an outlet for emotional and cognitive problem solving, especially during a natural disaster. However, the mechanism for this problem-solving process has not been identified in prior literature. Using a theoretical lens derived from prior social psychology literature, we advance two theoretical explanations of catharsis, with competing outcomes. One explanation holds that catharsis arises from resolving personal problems with others. A second explanation holds that catharsis arises from disclosing feelings to others. Using data from 183 Twitter users, we test these two theories in two time periods: during a natural disaster, in the response period, and after the natural disaster, during the recovery period. We find significant differences in catharsis response between the two periods.